2016
DOI: 10.1016/j.otsr.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Is there a benefit for health care workers in testing HIV, HCV and HBV in routine before elective arthroplasty?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Studies in proxy populations included several large studies analysing test results of HBV screening during pregnancy and the national blood donor surveillance. Other evidence for the GP was mostly derived from large cross-sectional screening studies in hospital emergency departments or medical practices [25,32,36,50,100,114,115]. All these populations may represent the GP but it should be taken into account, that there might be a selection bias as population groups possibly differ in health care-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in proxy populations included several large studies analysing test results of HBV screening during pregnancy and the national blood donor surveillance. Other evidence for the GP was mostly derived from large cross-sectional screening studies in hospital emergency departments or medical practices [25,32,36,50,100,114,115]. All these populations may represent the GP but it should be taken into account, that there might be a selection bias as population groups possibly differ in health care-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that HIV screening before elective orthopaedic surgery, especially for patients with risk factors, may be beneficial to surgeons [19,20]. Amongst healthcare workers, surgeons have the highest incidence of exposure reported as approximately 12 percutaneous blood exposures per person per year [21].…”
Section: Introductionmentioning
confidence: 99%
“…Winkelmann and colleagues [3] examined a population of patients undergoing elective joint replacement to determine whether preoperative screening was worth the costs of identifying infections. In the 1534 patients screened, they found 21 patients with hepatitis C, 10 patients with hepatitis B, and one patient with HIV infection.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Each newly diagnosed infection cost 7250 euros. The authors estimated ''the risk of hepatitis C transmission from an index patient with unknown status of infectiousness to health care worker after percutaneous contact to blood is [3].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%